Bacillus-based inoculants enhance drought resilience in soybean: agronomic performance and remote sensing analysis from multi-location trials in Brazil - Vasconcelos, Julio Cezar Souza; Arantes, Caio Simplicio; Gomes, Eliane Aparecida; Oliveira-Paiva, Christiane Abreu de; de Sousa, Sylvia Morais; Speranza, Eduardo Antonio; Antunes, João Francisco Gonçalves; Lana, Ubiraci Gomes de Paula; Cançado, Geraldo Magela de Almeida (Frontiers in Plant Science, 2025)
Climate change exacerbates drought stress, posing challenges to global soybean grain yield. This study assesses the effectiveness of microbial inoculants derived from two Bacillus velezensis (strains 5D5, 6E9) and one Bacillus subtilis (strain 1A11), which were previously selected in vitro to promote growth and enhance drought resilience in soybeans (Glycine max [L.] Merr.), and evaluated through agronomic metrics and remote sensing. A greenhouse experiment was conducted to evaluate the performance of these inoculants under both irrigated and drought conditions. The inoculants were applied at the dose-range of 1, 2, 3 and 4 mL Kg-1 of seed to identify the optimal dose. The greenhouse results indicated that for many tested doses, the three bacterial strains significantly increased shoot fresh weight, shoot dry weight, and root dry weight compared to control treatments. Multi-location field-trials in Brazil (Birigui, Itapira and Piracicaba) were conducted during the growing seasons of 2022–2023 and 2023–2024, using 3 mL Kg-1 of seed as a reference dose. These field-trials revealed yield improvements of 11.3 to 18% for inoculated treatments, with B. subtilis 1A11 achieving the highest grain yield of 620 Kg ha-1 over the control. However, all three microbial inoculants significantly enhanced soybean development and grain yield relative to non-inoculated controls. Vegetation indices, particularly the Enhanced Vegetation Index 2 (EVI2), derived from PlanetScope satellite and Unmanned Aerial Vehicle (UAV) imagery, demonstrated a high overlap between field data and model predictions, confirming the value of remote sensing as a predictive tool. Climatic variability significantly impacted the yield in field-trials, with 2022–2023 (4.28 t ha-1 outperforming 2023–2024 (3.34 t ha-1) due to higher temperatures (>40 °C) and lower rainfall in the last season. Meanwhile, locations with balanced precipitation, like Itapira, showed superior grain yield. Statistical modeling confirmed inoculant efficacy and EVI2's utility in production measurement. This study emphasizes that microbial inoculants can serve as sustainable strategies to mitigate the impacts of drought. By integrating Bacillus-based bioinoculants into soybean cultivation and utilizing both agronomic and remote sensing metrics for validation, we can enhance resilience and ultimately support food security amid climate variability.